Trial By Fire - Steel, Danielle (New York : Delacorte, 2024)
"In this inspiring novel from #1 New York Times bestselling author Danielle Steel, the life of a Parisian woman changes in a heartbeat when she's trapped by wildfires in Napa Valley"--.
new book 2024 fall.
Keywords: Women; Wildfires; Family life; Romance; Contemporary; Napa Valley, Calif; Novels